Cytomegalovirus Genotype Distribution among Congenital and Perinatal Infected Patients with CMV-Associated Thrombocytopenia. (7th February 2022) - Hu, Hongbo; Peng, Wenwen; Peng, Qiaoying; Cheng, Ying
Abstract: Objective: We determined the prevalence and relationship of glycoprotein B (gB), glycoprotein N (gN), and glycoprotein H (gH) genotypes of cytomegalovirus (CMV) in CMV-associated thrombocytopenia (CAP). Methods: CMV gB, gN, and gH strains were determined by nested PCR and restriction length polymorphism from 24 CAP and 20 asymptomatic CMV infected infants. Results: The order of prevalence was gB1 (70.8%, 17/24), gN4 (45.8%, 11/24) and gH2 (54.2%, 13/24). There was a greater prevalence of gB1(75.0%, 15/20), gN4(50.0%, 10/20) and gN2 (35.0%, 7/20) in moderate to severe infection ( p = 0.014 and p = 0.003). By logistic regression, gH2 ( p = 0.031) had an elevated risk of thrombocytopenia. Reduced risks of thrombocytopenia were associated with gB2 ( p = 0.020), gN1 ( p = 0.018) and gN3 ( p = 0.008). The most virulent were gB1 ( p = 0.033) and gN2 ( p = 0.038). Conclusions: There may be a potential association between the gH2 genotype of CMV and infantile thrombocytopenia.